Effects of caatinga propolis from Mimosa tenuiflora and its constituents (santin, sakuranetin and kaempferide) on human immune cells - Sartori, Arthur Alves [UNESP]; Son, Ninh The; da Silva Honorio, Mariana [UNESP]; Ripari, Nicolas [UNESP]; Santiago, Karina Basso [UNESP]; Gomes, Anderson Moreira [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Bastos, Jairo Kenupp; Sforcin, José Maurício [UNESP] (Elsevier, 2024)
Ethnopharmacological relevance: Propolis is a bee product used in folk medicine to treat inflammatory diseases. Diverse types of propolis are produced worldwide depending on the local flora. Recently, research has been focused on a propolis sample produced in the northeast Brazilian “caatinga” from Mimosa tenuiflora, popularly known as “jurema-preta”. Aim of the study: A possible immunomodulatory/anti-inflammatory action was analyzed to verify the potential of M. tenuiflora propolis (MP) and its constituents (santin, sakuranetin and kaempferide) in human immune cells under baseline conditions or in LPS-stimulated cells. Methods: Cell viability, cytokine (TNF-α, IL-1β, IL-6, IL-8, IL-10) production and intracellular pathways (NF-kB and p38 MAPK) were evaluated. Results: Under basal conditions, MP and sakuranetin did not affect cytokine production; santin enhanced TNF-α, IL-1β, IL-6, while kaempferide inhibited IL-8 and IL-10. In LPS-stimulated cells, MP and its compounds exerted an inhibitory activity on TNF-α and IL-1β, while no effects were seen on IL-6 and IL-8. Santin and kaempferide inhibited IL-10 production. No significant differences were seen on NF-kB and p38 MAPK intracellular pathways. Conclusion: Data indicated the immunomodulatory action of caatinga propolis and its constituents at noncytotoxic concentrations, specifically an anti-inflammatory activity in LPS-treated cells by inhibiting cytokine production. Santin, sakuranetin and kaempferide appeared to be involved in MP activities.
Keywords: Caatinga; Immune cells; Inflammation; Isolated constituents; Propolis